Fermentation conditions of Streptomyces tuirus isolated from the rhizosphere of Origanum majorana to produce antibacterial metabolites against MRSA - Mona Tfaily, Jamilah Borjac (Journal of Applied Pharmaceutical Science, 2024)
Methicillin-resistant Staphylococcus aureus (MRSA) is one of the pathogenic bacteria that poses a major risk to public health as it is resistant to many antibiotics. Therefore, this study was conducted to assess the effect of cultural and nutritional conditions to enhance the production of bioactive compounds against MRSA by Streptomyces tuirus isolated from the rhizosphere of Origanum majorana. Streptomyces tuirus was subjected to submerged fermentation across various culture media and under diverse growth conditions, including variations in temperature, duration, agitation speed, carbon, and nitrogen sources. The mass of crude extract obtained was measured under diverse conditions. The agar well diffusion method was utilized to measure the antibacterial activity of the extract against MRSA. Results showed that using Starch Casein Broth (SCB) with 7 days of incubation at 30°C, and 150 rpm agitation speed yielded the best antibacterial activity against MRSA. Additionally, the supplementation of glucose (1%) as a carbon source and sodium nitrate (1%) as a nitrogen source to SCB resulted in the production of an extract with the highest activity. This study showed that S. tuirus grown in SCB supplemented with glucose and sodium nitrate enhances the production of antimicrobial compounds against MRSA.
Keywords: Streptomyces, MRSA, optimization, antibacterial activity, crude extract, mass